Activities of Amphioxus GH-Like Protein in Osmoregulation: Insight into Origin of Vertebrate GH Family - Mengyang Li; Chengyan Jiang; Yu Zhang; Shicui Zhang (International Journal of Endocrinology)
GH is known to play an important role in both growth promotion and osmoregulation in vertebrates. We have shown that amphioxus possesses a single GH-like hormone (GHl) gene encoding a functional protein capable of promoting growth. However, if GHl can mediate osmoregulation remains open. Here, we demonstrated clearly that GHl increased not only the survival rate of amphioxus but also the muscle moisture under high salinity. Moreover, GHl induced the expression of both the ion transporter Na+-K+-ATPase (NKA) and Na+-K+-2Cl− cotransporter (NKCC) in the gill as well as the mediator of GH action IGFl in the hepatic caecum, indicating that GHl fulfills this osmoregulatory activity through the same mechanisms of vertebrate GH. These results together suggest that the osmoregulatory activities of GH had emerged in the basal chordate amphioxus. We also proposed a new model depicting the origin of pituitary hormone family in vertebrates.